O podatku, informaciji in znanju - Mohorič, Tomaž (Uporabna informatika (Ljubljana), 1999)
the terms data and information are often used as a synonyms in spite og quite a big sematic difference between them. Similar destiny shares the term knowledge, which ist often used in place of therm data. The intention of this article is to advocate that each term mentioned has its own meaning. First, the human way of making perceptions, conceptions, and representations is thoroughly described, followed by some standard definitions of data, information, and knowledge.
Keywords: definicije; informacija; podatek